Prevalence and reasons for missed dental appointments among patients treated by undergraduate dental students of Universiti Sains Islam Malaysia - Khairuddeen, Nur Farah Insyirah; Ahmad Nazari, Nur Haifa Najihah; Ali Al-Kadhim, Aws Hashim; Samsudin, Ahmad Dzulfikar; Amran, Norashikin; Abdul Hamid, Nor Faharina; Jaafar, Azlan (IIUM Journal of Orofacial and Health Sciences, 2022)
Missed dental appointments drastically affect treatment proficiency and productivity of dental care facility. This study aimed to determine the prevalence and reasons for missed dental appointments among patients treated by clinical dental students of Universiti Sains Islam Malaysia (USIM). A total of 202 folders from year 2018 to 2020 treated by year 3 to year 5 dental students were retrieved from a pool of patient’s record files using simple random sampling methods. Information on missed appointments was recorded. Other patients’ information was kept confidential. The percentage of missed dental appointments among patients under clinical dental students’ care was 37.1% (95% CI=30.7, 44.0). The majority of patients who missed dental appointments were male (37.6%), adults (38.7%) and employee (40.2%) patients. The most reported reason for the missed dental appointment was due to personal matters (36%) and the least was forgetfulness (0.6%) and miscommunication (0.6%). In conclusion, missed dental appointment commonly occurs among patients and frequently it was due to personal matters. A proper explanation by the students before scheduling an appointment is crucial to avoid any future missed dental appointments.